2016
DOI: 10.1525/mp.2016.33.5.571
|View full text |Cite
|
Sign up to set email alerts
|

Audio Features Underlying Perceived Groove and Sensorimotor Synchronization in Music

Abstract: The experience of groove is associated with the urge to move to a musical rhythm. Here we focus on the relevance of audio features, obtained using music information retrieval (MIR) tools, for explaining the perception of groove and music-related movement. In Study 1 we extracted audio features from clips of real music previously rated on perceived groove. Measures of variability, such as the variance of the audio signal’s RMS curve and spectral flux (particularly in low frequencies), predicted groove ratings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
117
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 37 publications
11
117
1
Order By: Relevance
“…They found that beat salience (the acoustical markedness of the regular beat in the audio signal) and event density were positively associated with the groove ratings: music with an acoustically salient regular beat and high event density had a tendency to obtain high groove ratings. The results on beat salience were largely confirmed by Stupacher et al in 2016 [ 77 ] who additionally found that high sound intensity in the lowest bass range was positively associated with groove. Also in 2016, Wesolowski & Hofmann [ 78 ] studied 198 excerpts from electronic dance music and found that stimuli with a non-isochronous bass and high rhythmic variability in the upper frequency domain were positively evaluated by listeners, compared to stimuli that did not show these characteristics.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…They found that beat salience (the acoustical markedness of the regular beat in the audio signal) and event density were positively associated with the groove ratings: music with an acoustically salient regular beat and high event density had a tendency to obtain high groove ratings. The results on beat salience were largely confirmed by Stupacher et al in 2016 [ 77 ] who additionally found that high sound intensity in the lowest bass range was positively associated with groove. Also in 2016, Wesolowski & Hofmann [ 78 ] studied 198 excerpts from electronic dance music and found that stimuli with a non-isochronous bass and high rhythmic variability in the upper frequency domain were positively evaluated by listeners, compared to stimuli that did not show these characteristics.…”
Section: Introductionsupporting
confidence: 65%
“…Witek et al [ 5 ] considered listeners’ familiarity with traditionally groove-related styles, but did not measure an association between familiarity and groove ratings. Stupacher et al [ 77 ], in their second study, investigated whether listeners’ groove ratings were influenced by their familiarity with the music, but did not observe such an influence either. Recently, Madison & Schiölde [ 82 ] found that repeated exposure to music (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research has moved on to discuss other musical aspects that promise to be relevant for groove, besides microtiming. Beat salience, event density and pulse clarity have been identified as possible sources for (or at least correlates of) groove (Madison et al, 2011 ; Stupacher et al, 2016 ). Several studies have shown that syncopation is associated with the experience of groove (Madison and Sioros, 2014 ; Sioros et al, 2014 ; Witek et al, 2014 ) and with body movement (Witek et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Movements such as body sway, head nodding, and foot tapping frequently emerge while listening to music in our daily lives. The feeling that induces body movement has been defined as groove (Pressing, 2002 ; Madison, 2006 ; Madison et al, 2011 ; Janata et al, 2012 ; Stupacher et al, 2013 , 2016 ; Leow et al, 2014 ; Ross et al, 2016 ; Witek et al, 2017 ). The link between groove and movement suggests that there may be an optimal tempo at which groove exists.…”
Section: Introductionmentioning
confidence: 99%